Green Regio‐ and Enantioselective Aminolysis Catalyzed by Graphite and Graphene Oxide under Solvent‐Free Conditions. Issue 11 (17th May 2016) - Acocella, Maria Rosaria; D'Urso, Luciana; Maggio, Mario; Guerra, Gaetano
Abstract: The ring‐opening reactions of epoxides with amines were efficiently and regioselectively catalyzed by high‐surface‐area graphite and graphene oxide under metal‐free and solvent‐free conditions. For epoxides without aryl groups, catalytic activity was observed only for graphene oxide, and hence, the activity must have been due to its acidic groups. For styrene oxide, instead, graphite and graphene oxide exhibited rather similar catalytic activities, and hence, the activity was mainly due to activation of the electrophilic epoxide by π‐stacking interactions with the graphitic π system. The described aminolysis procedure is green and cheap because the catalyst can be recovered and recycled without loss of efficiency. Moreover, these heterogeneous catalysts exert high stereoselective control in the presence of nonracemic epoxides and provide chiral β‐amino alcohols with enantiomeric excess values up to 99 %. Abstract : Open up ! The ring‐opening reactions of epoxides with amines are regioselectively catalyzed by high‐surface‐area graphite and graphene oxide under metal‐free and solvent‐free conditions. The catalyst can be recovered and recycled without loss of efficiency. These catalysts also exert high stereoselective control in the presence of nonracemic epoxides and provide chiral β‐amino alcohols with enantioselectivities up to 99 %.